Improvement of technological processes of cultivation of vegetable crops in the Far East. Review - N. A. Sakara; T. S. Tarasova; V. I. Oznobikhin (Овощи России, 2023)
The results of the selection work of the Primorsky vegetable experimental station, work in the field of seed production of vegetable crops are presented, the characteristics of the negative processes occurring in the arable soils of the region and their removal by the developed ridgeridge technology of cultivation by technical means with a wide base are given. A comparative characteristic of the former and the wide-row version in terms of energy consumption and fuel consumption is givenAuthors´ Contribution: All authors contributed to the planning and setting up the experiment, aswell as in the analysis of experimental data and writing of the article.Based on the results of the selection work of the Primorsky Vegetable Experimental Station for the period 1993-2023, the station bred and released 56 varieties and hybrids of 19 main vegetable crops. The experience of the Primorsky branch of the Federal scientific vegetable center allows organizing production at a modern level, taking into account the rich experience of other regions of Russia. In conditions of monsoon climate and soils of heavy granulometric composition, with a general lack of heat, their fertility is negatively affected by a large number of external factors. To grow vegetables, a set of measures is needed for serious drainage and irrigation reclamation (creation of polder systems with the laying of systematic plastic drainage) against the backdrop of ridge-ridge cultivation technology, fine irrigation system). The developed wide-cut technology and a set of machines make it possible to introduce a resource-saving technology that saves energy costs and fuel.